2021
DOI: 10.2298/jsc210521059e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Fe3O4/PEG-400/oxalic acid magnetic nanoparticles as a heterogeneous catalyst for the synthesis of pyrrolin-2-ones derivatives

Abstract: In this study, oxalic acid has been successfully loaded on Fe3O4/PEG-400 under ultrasonic irradiation and Fe3O4/PEG/oxalic acid as a new nanomagnetic catalyst has been synthesized. The chemical structure of the catalyst has been investigated by FT-IR spectrum, XRD, EDX and SEM methods. The catalyst has been used for the synthesis of 3-acyl-5-hydroxy-3-pyrrolin-2-one derivatives from the corresponding aldehydes, anilines and dimethyl acetylenedicarboxylate (DMAD) by one-pot and three-component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…1 H - 13 C HSQC spectrum showed that protons resonance at 1.86 ppm, 3.01 ppm, and 5.81 ppm correlate with carbons resonance at 15.35 ppm, 30.34 ppm, and 61.13 ppm, respectively. Therefore, peaks at 15.35 ppm, 30.34 ppm, and 61.13 ppm in 13 C NMR spectrum correspond to C7, C8, and C5, respectively. Besides, there were also other cross peaks resulted from the correlation between aromatic protons and aromatic carbons which are directly attached to each other (Figure 9).…”
Section: Figure 8 1 H Nmr Spectrum Of 4-(1-methylamino)ethylene-5phen...mentioning
confidence: 97%
See 2 more Smart Citations
“…1 H - 13 C HSQC spectrum showed that protons resonance at 1.86 ppm, 3.01 ppm, and 5.81 ppm correlate with carbons resonance at 15.35 ppm, 30.34 ppm, and 61.13 ppm, respectively. Therefore, peaks at 15.35 ppm, 30.34 ppm, and 61.13 ppm in 13 C NMR spectrum correspond to C7, C8, and C5, respectively. Besides, there were also other cross peaks resulted from the correlation between aromatic protons and aromatic carbons which are directly attached to each other (Figure 9).…”
Section: Figure 8 1 H Nmr Spectrum Of 4-(1-methylamino)ethylene-5phen...mentioning
confidence: 97%
“…One of the most common methodologies for the construction of the skeleton of substituted 3-hydroxy-1,5dihydro-2H-pyrrol-2-ones is based on one-pot multicomponent reactions of aromatic aldehydes, arylamines and acetylenedicarboxylate in the presence of an acid catalyst [11], [12], [13], [14]. However, 3-pyrroline-2-one derivatives obtained from this method contain alkoxycarbonyl group (−COOR) at the 4-position and therefore, these nitrogen-containing five-membered rings could only be functionalized with nucleophilic amine at the 3-position.…”
Section: Figure 2 Naturally Occurring 15-dihydro-2h-pyrrol-2-ones Der...mentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-component reactions (MCRs) are efficient synthetic strategies in which three or more starting materials react in a single flask to obtain new products containing important portions of all reactants [21]. 1,5-Disubstituted-4-ethoxycarbonyl-3-hydroxy-3-pyrroline-2-ones have been synthesized via MCRs of substituted benzaldehydes, amines, and diethyl acetylenedicarboxylate [22], [23], [24], [25]. In addition, 1,5-disubstituted-4-ethoxycarbonyl-3hydroxy-3-pyrroline-2-ones could also be synthesized via MCRs of substituted benzaldehydes, amines and sodium diethyl oxalacetate [26], [10].…”
Section: Figure 2 Natural Compounds Containing 15-dihydro-2h-pyrrol-2...mentioning
confidence: 99%
“…This kind of reaction has been proven to be an efficient synthetic pathway to obtain structurally complicated and biologically active products containing substantial portions of all starting materials [27]. Recently, polysubstituted 3-hydroxy-1,5-dihydro-2H-pyrrol-2ones have been synthesized via eco-friendly multicomponent reactions of aromatic aldehydes, amines, and dialkyl acetylenedicarboxylate or sodium diethyl oxalacetate [28][29][30][31][32][33][34]. The resulting products have the 4-position locked by the alkoxycarbonyl (-COOR) group and these 2-pyrrolidinone derivatives can be functionalized with amines as nucleophiles via the 3-position [10, [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%